N.A. Nazarbayev and the Problem of Nuclear Weapons in the History of Independent Kazakhstan (1991-1995). / N. A. Nazarbayev y el problema de las armas nucleares en la historia de Kazajstán independiente (1991-1995) - Karasayev, Gani M.; Yensenov, Kanat A.; Dyusen, Seitkali Z.; Aminov, Talgatbek M.; Kaliev, Zhabay N. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT Research is devoted to the problem of nuclear weapon. Scientific literature, archive data, analyzes of international relations and events of world level related to this problem have been analyzed. The cases related to the closing of Semey nuclear test which was erected in the year 1949 in Kazakhstan, and had had the explosions until 1990s, and the entire range of nuclear weapons left from the Soviet Union were analyzed. The article is aimed at proving the importance of non-proliferation of nuclear weapons to other countries, gradual elimination of this weapon and stop the work in the test sites and use of the atom only for peaceful purposes.RESUMEN La investigación está dedicada al problema de las armas nucleares. Se han analizado literatura científica, datos de archivo, análisis de relaciones internacionales y eventos a nivel mundial relacionados con este problema. Los casos relacionados con el cierre de la prueba nuclear de Semey, que fue erigida en el año 1949 en Kazajstán, y que había tenido las explosiones hasta la década de 1990, y toda la gama de armas nucleares dejadas en la Unión Soviética fueron analizados. El objetivo del artículo es demostrar la importancia de la no proliferación de las armas nucleares en otros países, la eliminación gradual de esta arma y poner fin a la labor en los lugares de ensayo y el uso del átomo sólo con fines pacíficos.